Different Aberrant Changes of mGluR5 and Its Downstream Signaling Pathways in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Hu, Chao; Chen, Cao; Xia, Ying; Chen, Jia; Yang, Wei; Wang, Lin; Chen, Dong-Dong; Wu, Yue-Zhang; Fan, Qin; Jia, Xiao-Xi; Xiao, Kang; Shi, Qi; et al. (Frontiers in Cell and Developmental Biology, 2022)
Metabotropic glutamate receptor subtype 5 (mGluR5) is a G-protein-coupled receptor found widely in the central nervous system. It has been involved in the development and progression of some neurodegenerative diseases, but its role in prion diseases is rarely described. In this study, the changes of mGluR5 and its downstream signaling pathways in prion infected cell line SMB-S15 and the brains of scrapie infected experimental rodents were evaluated by various methodologies. We found the levels of mGluR5 were significantly increased in a prion-infected cell line SMB-S15 and the cultured cells transiently expressing an abnormal form PrP (Cyto-PrP). Using immunoprecipitation tests and immunofluorescent assays (IFA), molecular interaction and morphological colocalization between PrP and mGluR5 was observed in the cultured cells. We identified that the (GPCRs)-IP3-IP3R-Ca2+ pathway was activated and the levels of the downstream kinases p38, ERK and JNK were increased in SMB-S15 cells. After treated with mGluR5 antagonist (MTEP) or removal of prion replication by resveratrol in SMB-S15 cells, the upregulations of mGluR5 and the downstream kinases restored in a certain degree. Moreover, increased mGluR5 contribute to the cell damage in prion infected cells. Contrarily, the levels of mGluR5 in the brains of several scrapie-infected rodent models were decreased at terminal stage. IFA of the brain sections of scrapie-infected rodents demonstrated that the signals of mGluR5 were preferentially colocalized with the NeuN-positive cells, accompanying with severe neuron losses in Nissl staining, which might be a reason for the decrease of mGluR5. Our data indicate the different aberrant alterations of mGluR5 and the downstream signaling pathways during prion infection in vivo and in vitro.